Making room: Facilitating the testimony of child witnesses and victims - Authors: Commissioned by the Centre for Child Law, University of Pretoria (Pretoria University Law Press (PULP), 2015)
About the publication Court rooms are frightening places for anyone testifying. Even adults are fearful about giving evidence in front of magistrates and judges, and about being questioned by prosecutors and defence lawyers. Imagine how much more scary that must be for a child. Even worse, in sexual offences children have to talk about embarrassing things, for which they do not even have an adequate or accurate vocabulary. South African law has excellent provisions which allow children to testify via intermediaries and in separate rooms, so that they need not encounter the offender. But this is only as good as the provisioning allows. In the 2009 case of Director of Public Prosecutions v the Minister of Justice and Constitutional Development, the Court laid emphasis on these special arrangements, and at the time directed the Minister of Justice to place a report before the Constitutional Court on the readiness of the courts to provide the specialised services. Five years on, this report looks at the statistical evidence that is currently available, coupled with empirical evidence gathered from visits to sexual offences court, to determine how much progress has been made towards the goal of children being able to testify in a safe, child-friendly environment. About the authors: The Centre for Child Law was established in 1998 and is based in the Faculty of Law at the University of Pretoria. The Director of the Centre is Prof Ann Skelton. The Centre contributes towards the establishment and promotion of the best interests of children in South Africa through litigation, advocacy, research and education. Table of Contents FOREWORD ACKNOWLEDGMENTS Introduction Background Quantifying compliance: Where we were compared to where we are 3.1 Intermediaries 3.2 Separate child witness testifying rooms 3.3 CCTV systems 3.4 One-way mirrors Reported experiences: A qualitative view of court services for child victims and witnesses 4.1 Eastern Cape 4.1.1 Lusikisiki Court 4.1.2 Engcobo Court 4.1.3 Qumbu Court 4.1.4 Ngqeleni Court 4.1.5 Mthatha Court 4.1.6 Concluding reflections on the Eastern Cape 4.2 Free State 4.2.1 Welkom Court 4.2.2 Odendaalsrus Court 4.2.3 Bothaville Court 4.2.4 Concluding reflections on the Free State 4.3 Gauteng 4.3.1 Cullinan Court 4.3.2 Bronkhorstspruit Court 4.3.3 Krugersdorp Court 4.3.4 Palm Ridge Court 4.3.5 Pretoria North Court 4.3.6 Concluding reflections on Gauteng 4.4 KwaZulu-Natal 4.4.1 Durban Court 4.4.2 Camperdown Court 4.4.3 Pinetown Court 4.4.4 Verulam Court 4.4.5 Pietermaritzburg Court 4.4.6 Concluding reflections on KwaZulu-Natal 4.5 Limpopo 4.5.1 Sibasa Court 4.5.2 Giyani Court 4.5.3 Louis Trichardt Court 4.5.4 Concluding reflections on Limpopo 4.6 Mpumalanga 4.6.1 Middelburg Court 4.6.2 Ermelo Court 4.6.3 Nelspruit Court 4.6.4 Mhala Court 4.6.5 Concluding reflections on Mpumalanga 4.7 North West 4.7.1 Brits Court 4.7.2 Mmabatho Court 4.7.3 Lehurutshe Court 4.7.4 Zeerust Court 4.7.5 Lichtenburg Court 4.7.6 Concluding reflections on the North West 4.8 Northern Cape 4.8.1 Barkly West Court 4.8.2 Warrenton Court 4.8.3 Hartswater Court 4.8.4 Douglas Court 4.8.5 Kimberley Court 4.8.6 Concluding reflections on the Northern Cape 4.9 Western Cape 4.9.1 Atlantis Court 4.9.2 Parow Court 4.9.3 Wynberg Court 4.9.4 Paarl Court 4.9.5 Cape Town Court 4.9.6 Concluding reflections on the Western Cape Survey results: Observations and some recommendations 5.1 Lack of accommodation 5.2 Intermediaries 5.2.1 Skills and competency 5.2.2 Debriefing of intermediaries 5.2.3 Evaluation of intermediaries' performance 5.2.4 Appointment of intermediaries - Contract 5.3 Awareness of the needs of child victims and witnesses 5.4 Lack of toys and other means to keep children busy 5.5 Lack of refreshments for child victims and witnesses Concluding recommendations